Pengaruh Job Demands, Job Resources, Dan Job Involvement Terhadap Job Satisfaction - Muhamad Izdad Fuadi; Nur Hidayah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine and analyze the effect of job demands, job resources, and job involvement on employee job satisfaction. Job demands affect job satisfaction, job resources affect job satisfaction, and job involvement affects job satisfaction. The population in this study were employees of the Department of Tourism, Youth and Sports, Magelang Regency. The sample taken in this study were 45 employees with saturated sampling. The analytical tool used is Multiple Linear Regression. The results of this study indicate that job demands have a positive and significant effect on job satisfaction. Job resources have a positive effect on job satisfaction. Job involvement has a positive and significant effect on job satisfaction. Job demands, job resources, and job involvement have an influence of 84.4% on job satisfaction, while the remaining 15.6% is influenced by other variables.